Enzymatic hydrolysis preparation and activity analysis of antioxidant peptides derived from walnut dregs - NI Ce; CAO Tianhong; CHEN Min; YU Xun; WU Hao; WEN Li (Shipin yu jixie, 2024)
Objective: This study focused on the identification and activity analysis of antioxidant active peptides in walnut dregs protein hydrolysates. Methods: Protein was extracted from walnut meal by fractionation method, and five kinds of proteolytic enzymes, including trypsin, papain, neutral protease, alkaline protease and flavor protease, were used to hydrolyze the proteins. The antioxidant activity of trypsin hydrolysate （TH）, papain hydrolysate （PH）, dispase hydrolysate （DH）, alcalase hydrolysate （AH） and flavourzyme hydrolysate （FPH） were evaluated and compared. The in vitro antioxidant activity of different concentrations of AH was determined by the detection indexes of DPPH free radical scavenging rate, ABTS free radical scavenging rate and hydroxyl free radical scavenging rate. The sequences of all peptides in AH were identified by LC-MS/MS technology, and the potential antioxidant active peptides of walnut were screened by PeptideRanker, BIOPEP-UWM database and molecular docking tool AutoDock1.5.6, and the two antioxidant active peptides were obtained. The above two peptides were simulated with Keap1 protein, and the antioxidant activity of the two antioxidant peptides was analyzed by using the zebrafish embryo oxidative damage model. Results: The optimal scavenging rates of AH with better antioxidant activity among the five enzymatic hydrolysates were （71.56±0.75）%, （60.63±0.45）% and （98.63±0.06）%, respectively. LC-MS/MS was identified by computer analysis to obtain two active ALWPF and PLRWPF peptides, both of which could bind to the active sites of Keap1 protein, with binding energies of -9.2 and -9.6 kJ/mol, respectively. The safe concentrations of zebrafish embryos treated with ALWPF and PLRWPF peptides ranged from 0～50 μg/mL and 0～30 μg/mL, respectively. Conclusion: Two antioxidant peptides were obtained from walnut meal, and the antioxidant effects of them were verified by zebrafish embryo model. The results of this study can provide a basis for the in-depth utilization of walnut protein.